The Influence Of Halal Knowledge, Halal Awareness, Religiosity On Food Beverages Purchase Decisions Among Generation Z - Suci Maulidya; Fira Nurafini (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The dominance of the consumer market in Indonesia, now led by Generation Z Muslims, presents the culinary industry with the challenge of meeting food needs in accordance with sharia principles. In rapidly developing urban areas such as Surabaya, the dynamics of food and beverage consumption continue to soar, but have not been matched by the even distribution of official halal certification for every culinary product in circulation. Field conditions demonstrate this phenomenon, where some young Muslim consumers are still ignorant and continue to consume products whose halal status is not guaranteed, reflecting their cognitive understanding and spiritual depth. This study applies an associative quantitative approach through primary data collection from 131 respondents domiciled in Surabaya. Data were analyzed using techniques (SPSS) to test direct and indirect relationships between variables. The results of the complete test indicate that partially halal knowledge, halal awareness, and religiosity have a significant influence on purchasing decisions for halal food and beverage products. This study contributes to regulators and educational institutions in developing knowledge about halal in the food and beverage world for Generation Z.